PELATIHAN MANAJEMEN PEMELIHARAAN ITIK SECARA INTENSIF DI KECAMATAN WEDUNG KABUPATEN DEMAK - Widiyaningrum, Priyantini; Lisdiana, Lisdiana; Utami, Nur Rahayu (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
The training of intensive breeding management has been carried out for duck farmers at district Wedung - Demak, on July-August 2013. The training was conducted in three activities, namely: (a) the transfer of knowledge about technique of preparing duck feed by available material, intensive maintenance , and incubator hatching technique; (b) implementation of intensive maintenance for the fertile eggs product, and (c) the practice of using the hatching incubator. Participants were duck farmer at Mutih Kulon and Tedunan, that maintain their ducks with extensive (grazing method). The results showed that the 27 participants who took the training have never been participated in the training of duck management. The reason of farmer breeding with grazing method, because they follow the habits of their parents. Most participants know that the maintenance of grazing method is bad, and they know that the intensive maintenance will increase the profits. The Proximate analysis of ration duck showed that its composition has taught balanced feed criteria. Production of eggs in the intensive maintenance hatchability reached 92%, eventhough the experiment at the farmer level reached 70.5% only.